2004
DOI: 10.1093/pch/9.7.457
|View full text |Cite
|
Sign up to set email alerts
|

Body temperature measurement in paediatrics: Which gadget should we believe?

Abstract: Many decisions regarding the investigation and treatment of paediatric patients are determined by body temperature. In the 21st century, we still struggle to find a quick and convenient method that parents and health care workers can use to measure body temperature accurately.The goal of measuring body temperature is to approximate the core temperature, which is the temperature of the blood that bathes the temperature-regulating centre in the hypothalamus. However, there is a gradient between every body site w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…In contrast, the temperature of the rectum is directly related to blood flow through the splanchnic circulation. 1,15 Goic et al also found that weight was significantly associated with RATD in cats; 19 however, although this was significant on univariable analysis in our study, the significance was lost when multivariable analysis was performed.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In contrast, the temperature of the rectum is directly related to blood flow through the splanchnic circulation. 1,15 Goic et al also found that weight was significantly associated with RATD in cats; 19 however, although this was significant on univariable analysis in our study, the significance was lost when multivariable analysis was performed.…”
Section: Discussioncontrasting
confidence: 58%
“…Assessment of body temperature is an important part of the physical examination and the information obtained guides clinical decisions. Invasive contact devices such as oesophageal and pulmonary artery thermistors are considered the gold standard for assessing core body temperature; 13 however, these are not suitable for conscious veterinary patients and are reserved for anaesthetised or critical care cases. 2,4 Therefore, most feline and canine patients have their temperatures measured using contact thermometers against the rectal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Although many methods have been evaluated, including tympanic readings, axillary readings, and forehead chemical strips, an acceptable substitute for rectal readings has not been found (Robinson, 2004). Temperature measured via the pulmonary artery or esophagus may be the most accurate measurement of core temperature (Al‐Mukhaizeen et al., 2004), but these methods are impractical for clinical settings outside the operating room or intensive care unit.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the present study showed that the relationship between intraabdominal and rectal temperature is not constant under all (patho‐)physiological conditions (Robinson, ) and thus extrapolating from rectal directly to body core temperature requires caution. Particularly the different endotoxaemic situations yielded highly variable relationships between both temperature sites, hinting at a change in expansion of core temperature in the body.…”
Section: Discussionmentioning
confidence: 65%